Endocrine dysfunctions may be sequelae of snake bite - Kar, Kaushik; Mukherjee, Sandipan (Asian Journal of Medical Sciences, 2021)
Background: At present snakebite has become a serious health problem in India. The actual incidence of mortality and morbidity related to the snakebite are not reported properly. Further, the most neglected part is the long term endocrine dysfunctions in survivors of snake bite. Aims and Objectives: To evaluate serum fT4, TSH, cortisol, prolactin, and testosterone levels in snake bite survivors after 3 and 6 months of snakebite. Materials and Methods: Forty-five survivors of russels viper bite patients were selected for the study according to inclusion and exclusion criteria. Admitted patients were treated accordingly and discharged in stable condition. The hormonal status were analysed and they have been followed up after 3 and 6 months. Results: Significant decrease in serum cortisol and prolactin were observed in survivors of russels viper bite patients particularly in them whose mean serum creatinine was more than 1.2 mg/dl and systolic blood pressure was <110 mm of Hg and diastolic Blood pressure was < 70 mm of Hg. Conclusion: Measurement of long term hormonal status like serum cortisol and prolactin can be beneficial in survivors of hematotoxic snake bite patients.